Financial Support To Tourism Activities - Karimova A.M. (International Journal of Advanced Science and Technology, 2020)
This article deals with the activity of tourism as one of the most important activities contributing to an additional source of replenishment of the budget of the country and creating additional jobs. Despite the creation of such favorable conditions by the state, in the field there are a lot of problems. The article provides suggestions, which helped to increase investment and development in the industry.